Adoption of drip fertigation system and technical efficiency of cherry tomato farmers in Southern China. (1st December 2020) - Yang, Qian; Zhu, Yueji; Wang, Jianwen
Abstract: The Drip Fertigation System (DFS) is a resource conservation technology for agricultural production. However, it has been rarely used in China. This study attempts to examine the impact of the DFS on the technical efficiency of cherry tomato farmers in southern China, and identify the factors affecting farmers' adoption of the DFS in their plantation practice. Primary data with 442 respondents of cherry tomato growers from villages in Lingshui County was collected through stratified random sampling. The Propensity Score Matching method (PSM) was used to eliminate the self-selection bias of sampling farmers, and two groups (adopters and non-adopters) of the DFS with 140 respondents in each group were matched. The technical efficiency of the two groups of farmers was estimated by the Data Envelopment Analysis (DEA) separately. We find that the average technical efficiency of the DFS adopters is significantly higher than that of non-adopters, highlighting the positive role of the DFS in promoting efficient usage of production inputs for cherry tomato farmers. Then the Logistic model was used to identify the determinants of farmers' adoption of the DFS in farming practices. The results show that farmers' age, education, farm size and perceived helpfulness of their social network had a positive impact on farmers' adoption of the DFS, whereas factors including farmers' planting experience, off-farm work, skillfulness of contact person and conformity to others affected it negatively. Highlights: The DFS practice can significantly improve the technical efficiency of the cherry tomato production in southern China. As a non-economic factor, social network plays an important role in farmers' take-up decisions of the DFS. The DFS would contribute to China's transformation from extensive agriculture to sustainable development.